Engineering Photophenomena in Large, 3D Structures Composed of Self‐Assembled van der Waals Heterostructure Flakes. Issue 11 (17th August 2015) - Krishna, M. Bala Murali; Man, Michael K. L.; Vinod, Soumya; Chin, Catherine; Harada, Takaaki; Taha‐Tijerina, Jaime; Tiwary, Chandra Sekhar; Nguyen, Patrick; Chang, Patricia; Narayanan, Tharangattu N.; Rubio, Angel; Ajayan, Pulickel M.; et al.
Abstract : A photocapacitive, dissipationless, optoelectronic terahertz response is observed in robust 3D van der Waals heterostructured flakes of hexagonal boron nitride and graphene. The response is fundamentally distinct from that of the parent materials and can be tuned from insulating to photocapacitive to semiconducting by varying the composition. Such hybrid structures have broad implications for tunable optoelectronic materials and potential terahertz devices.